Experimental Study of M Sand Based Geopolymer Concrete in Construction Industry - Baghel, Ruchi; Chandrakar, Vinay Kumar Singh (International Journal of Scientific Research in Civil Engineering, 2020)
For the construction of any structure, Concrete is the main material. Concrete usage around the world is second only to water. The main ingredient to produce concrete is Portland cement. On the other side global warming and environmental pollution are the biggest menace to the human race on this planet today. The production of cement. means the production of pollution because of the emission of CO2 during its production. There are two different sources of CO2 emission during cement production. Combustion of fossil fuels to operate the rotary kiln is the largest source and other one is the chemical process of calcining limestone into lime in the cement kiln also produces CO2.In India about 2,069,738 thousands of metric tons of CO2 is emitted in the year of 2010. The cement industry contributes about 5% of total global carbon dioxide emissions. In this study we are designing M30 grade of concrete considering M-Sand as an replacement of Natural Sand, and preparing Geopolymer concrete using flyash waste product. In this study it is observed that utilization of M-sand and Sodium hydroxide solution with Supper-plasticizer (silicon-oxo-aluminate) enhances compressive strength and durability of concrete.